The distinction between political crimes and terrorist crimes in the Saudi system and comparative laws - Alktaishat, Khadija Abdul Hamid (Journal of Economic, Administrative and Legal Sciences, 2017)
Terrorist crime is associated with political crime in a number of elements, which have caused a lot of confusion between the two types and have made it difficult to distinguish between them. It has opened wide the door to different and contradictory interpretations and descriptions of the same act. The verb is interpreted according to its political interests. Or so-called policy of double standards, especially at the international level. The research aims to shed light on the distinguishing boundaries between political crimes and terrorist crimes in the Saudi regime and comparative laws. The research shows that the distinction between political crimes and terrorist crimes is very weak in comparison with the great confusion between them in the Saudi regime.
Keywords: discrimination; crimes; politics; terrorism; the Saudi regime; comparative laws